Mapping five novel interspecific hybrid sterility loci between Oryza sativa and Oryza meridionalis - Li, Jing (Breed Sci, 2018)
Oryza meridionalis is a potential source for improving Asian cultivated rice O. sativa via direct hybridization and backcrossing. However, hybrid sterility between O. sativa and O. meridionalis is the main barrier of reproduction hindering the transfer of favorable genes from O. meridionalis to O. sativa. To investigate the nature of hybrid sterility between O. sativa and O. meridionalis, three accessions of O. meridionalis were used as male parents to cross Dianjingyou 1, an O. sativa subsp. japonica cultivar following the backcross with the recurrent parent of Dianjingyou 1. Twenty pollen sterility NILs (BC(6)F(1)) were obtained and genotyped by using simple sequence repeat (SSR) markers distributed across the 12 rice chromosomes. The heterozygous markers were employed to genotype the corresponding segregation populations for mapping sterility genes. As a result, five novel loci for pollen sterility between O. sativa and O. meridionalis were identified and designated as S51(t), S52(t), S53(t), S54(t) and S55(t), respectively. The genetic behavior of five novel loci followed one-locus allelic interaction model. The disharmonious interaction between Asian cultivated rice allele and wild relative allele led to the partial or full abortion of male gametes for one parent allele in the heterozygotes. These results will be useful for elucidating the mechanism of interspecific hybrid sterility and further utilizing favorable genes from O. meridionalis for enhancement of rice breeding.